An Efficient Approach and Procedure to Solve Customer Complaints Based on Combined Rasterization of Geography Information System - Qiang Chen; Sheng Jie Chen; Wei Guo; Jin Li (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
To solve customer complaints better for some telecommunication enterprises, a new and efficient approach through combined rasterization of Geography Information System (GIS) is presented in this paper. By the combined rasterization of surface features and landforms, the historical customer complaints and the real-time running state of network will be utilized to handle new complaints simultaneously. Also, an innovative process to handle complaints is proposed, too. The utilization of method and process will shorten the time of processing routine customer complaints. The experimental results show that the efficiency to process customer complaints will be improved greatly and the operation expenditure on customer services for telecommunication operators will be also decreased than before. DOI: http://dx.doi.org/10.11591/telkomnika.v11i9.2279